Updated model-independent measurement of the strong-phase differences between D0 and D ¯ 0 → K S / L 0 π + π − $$ {\overline{\textrm{D}}}^0\to {\textrm{K}}_{\textrm{S}/\textrm{L}}^0{\uppi}^{+}{\uppi}^{-} $$ decays - The BESIII collaboration; M. Ablikim; M. N. Achasov; P. Adlarson; X. C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; et al. (Journal of High Energy Physics)
Abstract The strong-phase differences between D 0 → K S L 0 π + π − $$ D^0→ K_{S(L)}^0π^{+}{π}^{-} $$ and D ¯ 0 → K S L 0 π + π − $$ {\overline{D}}^0→ K_{S(L)}^0π^{+}{π}^{-} $$ decays are one of the most important inputs in measuring the CP violating angle γ via B − → DK − decays. They also play a key role in studies of charm mixing and indirect CP violation. In this paper, the strong-phase differences are determined in a model-independent way with quantum-correlated D 0- D ¯ 0 $$ {\overline{D}}^0 $$ decays from 7.93 fb −1 of e + e − annihilation data at s $$ \sqrt{s} $$ = 3.773 GeV by the BESIII experiment. These results are the most precise to date and are expected to significantly reduce associated uncertainties in determining the CP violating angle γ and related charm mixing parameters.